2019
DOI: 10.18488/journal.1.2019.94.304.317
|View full text |Cite
|
Sign up to set email alerts
|

Causality between Financial Inclusion and Agricultural Sector Output in Nigeria

Abstract: Financial inclusionPrime lending rate Deposit rate Agricultural credit guarantee Scheme fund Demand deposit from rural areas and deposit money bank loan to small scale enterprises as a percentage of total loan. This study examines the causality between financial inclusion and Nigeria's agricultural sector output (AOG). Ex-post facto research design was used and the annual time series data for various years were obtained from the Central Bank of Nigeria's (CBN) Statistical Bulletin. The Unit Root Test, Engle -G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…They concluded that a significant and positive influence existed from spending on public goods on the per capita AGDP growth in Indonesia. Festus and Sebastine (2019) observed the linkage between produced agricultural goods and financial inclusion in Nigeria. The timeframe for their study was 1986-2017, and the tests included the unit root, the co-integration test of Engle-Granger, a model test of error correction (ECM) and a test of Granger causality.…”
Section: Financial Inclusion and Agricultural Growthmentioning
confidence: 99%
“…They concluded that a significant and positive influence existed from spending on public goods on the per capita AGDP growth in Indonesia. Festus and Sebastine (2019) observed the linkage between produced agricultural goods and financial inclusion in Nigeria. The timeframe for their study was 1986-2017, and the tests included the unit root, the co-integration test of Engle-Granger, a model test of error correction (ECM) and a test of Granger causality.…”
Section: Financial Inclusion and Agricultural Growthmentioning
confidence: 99%